Pemanfaatan Tanaman Obat Keluarga sebagai Minuman Penguat Imunitas Tubuh di RT 04 Kelurahan Bereng Pulang Pisau - Silvani Permatasari; Ervi Audina Munthe; Astrid Teresa; Fraulein Aryati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
WHO has declared COVID-19 a pandemic. Increasing body immunity is crucial for defense against infectious diseases. The immune system is influenced by several factors, including diet, environmental factors, lifestyle, age, stress, and hormones. Utilizing medicinal plants can make traditional drinks that are useful for increasing body immunity. The Ministry of Health Letter Statement No. HK.02.02/IV.2243/2020 concerning the Utilization of Traditional Medicines for Health Maintenance, Disease Prevention, and Health Care are attached with ingredients to increase body resistance. The community of RT 04 Bereng Village has a large area to grow family medicinal plants (TOGA) such as ginger, lemongrass, turmeric, Curcuma, and lime. These spices contain curcuminoid compounds which function as immunostimulators in boosting the immune system. In addition, herbs such as ginger, ginger, turmeric, and lemongrass contain high enough antioxidants so that they can ward off free radicals in our bodies. This service aims to provide information about processing TOGA into traditional drinks that can increase body immunity during the COVID-19 pandemic. This activity has stages of delivering education through pocketbooks, direct practice processing drinks from TOGA, and giving TOGA seeds. The results of this community service are in the form of herbal drinks, which are expected to increase the community's immunity; then can improve knowledge and skills in processing TOGA, especially in the neighborhood of RT 04 Kelurahan Bereng.